COMPOSIÇÃO DAS INFRACOMUNIDADES DE NEMATODA ENDOPARASITAS DE ASTYANAX LACUSTRIS (CHARACIFORMES: CHARACIDAE) NO CÓRREGO CURRAL DE ARAMES, DOURADOS, MS - Rojas, Mateus; Lopes, Douglas; Vieira, Kelly; Costa, Fábio (ANAIS DO ENIC, 2018)
-